Antioxidant and antiplatelet activity by polyphenol‐rich nutrients: focus on extra virgin olive oil and cocoa - Loffredo, Lorenzo; Perri, Ludovica; Nocella, Cristina; Violi, Francesco (British journal of clinical pharmacology, 2017)
Cardiovascular disease is the most common cause of death in the Western world. In the last decades nutraceutical approaches have been proposed to counteract atherosclerotic complications. In particular, polyphenols, a class of bio‐active molecules prevalently contained in foods such as cocoa, fruits, vegetables, wine and tea, have been widely studied for their beneficial properties. Several epidemiological and interventional studies have shown that polyphenol‐rich nutrients, as in extra virgin olive oil (EVOO) and cocoa, are associated with a risk reduction of cardiovascular events and/or modulation of cardiovascular risk factors. Definition of the mechanisms accounting for this putative cardio‐protective effect is still elusive. This review focuses on the mechanisms that may be implicated in the beneficial effects of EVOO and cocoa, including down‐regulation of oxidative stress and platelet aggregation, improvement of endothelial function and cardiovascular risk factor such as blood pressure, serum cholesterol and insulin sensitivity.